2012
DOI: 10.1002/chem.201201583
|View full text |Cite
|
Sign up to set email alerts
|

Two‐Dimensional Infrared Spectroscopy Reveals the Structure of an Evans Auxiliary Derivative and Its SnCl4 Lewis Acid Complex

Abstract: Determining the structure of reactive intermediates is the key to understanding reaction mechanisms. To access these structures, a method combining structural sensitivity and high time resolution is required. Here ultrafast polarization-dependent two-dimensional infrared (P2D-IR) spectroscopy is shown to be an excellent complement to commonly used methods such as one-dimensional IR and multidimensional NMR spectroscopy for investigating intermediates. P2D-IR spectroscopy allows structure determination by measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
21
1
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 14 publications
(27 citation statements)
references
References 38 publications
3
21
1
2
Order By: Relevance
“…[22,31] Die Polarisationsabhängigkeit der Kreuzsignale lässt Rückschlüsse auf den Winkel zwischen den Übergangsdipolmomenten der wechselwirkenden Schwingungen zu, was zur Strukturbestimmung genutzt werden kann. [32,33] Auch die anharmonische Kopplung,w elche aus den beobachteten anharmonischen Verschiebungen bestimmt wird, kann verwendet werden, um die molekulare Struktur abzuleiten. [34,4] Doch direkte anharmonische Kopplung ist nicht die einzige Mçglichkeit wie Kreuzsignale entstehen kçnnen.…”
Section: Methodsunclassified
See 1 more Smart Citation
“…[22,31] Die Polarisationsabhängigkeit der Kreuzsignale lässt Rückschlüsse auf den Winkel zwischen den Übergangsdipolmomenten der wechselwirkenden Schwingungen zu, was zur Strukturbestimmung genutzt werden kann. [32,33] Auch die anharmonische Kopplung,w elche aus den beobachteten anharmonischen Verschiebungen bestimmt wird, kann verwendet werden, um die molekulare Struktur abzuleiten. [34,4] Doch direkte anharmonische Kopplung ist nicht die einzige Mçglichkeit wie Kreuzsignale entstehen kçnnen.…”
Section: Methodsunclassified
“…Die Beispiele dieses Abschnitts zeigen, dass die Analyse von transienten Strukturen mittels T2D-IR bisher nur auf sehr grundlegendem Niveau betrieben wurde.H ingegen konnte man mit 2D-IR-Spektroskopie in Gleichgewichtssystemen bereits detaillierte Strukturanalysen durchführen. [31][32][33][34]83] T2D-IR-Spektroskopie kann solch detaillierte Information auch für transiente Spezies liefern, bei denen die hohe Zeitauflçsung von Femtosekundenspektroskopie ihren vollen Nutzen entfalten kann.…”
Section: Ausblickunclassified
“…All computations were performed by employing the program suite Gaussian 09, 25 using density functional theory (DFT) with Truhlar's hybrid meta-exchange-correlation functional M06 26 in conjunction with a 6-31+G(d,p) basis set. 1 Computations on Sn-containing species were performed using a 6-31+G(d,p) basis set with Stuttgart-Dresden effective core potentials (SDD) on the Sn atom. 27 Computations that use a DGDZVP basis set are reported in the ESI.…”
Section: Quantum Chemical Computationsmentioning
confidence: 99%
“…In a recent study we showed that polarization-dependent two-dimensional infrared (P2D-IR) spectroscopy is capable of resolving the conformation of small molecules in solution and their complexes with a catalyst. 1 Both, complex formation and dissociation are fast compared to the timescale of NMR. With its inherent (sub)picosecond time resolution and the high sensitivity of infrared spectroscopy, P2D-IR is a powerful technique to investigate the structure of short-lived intermediates.…”
Section: Introductionmentioning
confidence: 99%
“…Cross‐peaks can thus be used to disentangle and assign vibrational spectra of mixtures 22. 31 The polarization dependence of cross‐peaks gives the angle between the transition dipole moments of the interacting vibrations, which can be used to determine molecular structure 32. 33 The anharmonic coupling, which can be deduced from the observed anharmonic shifts, can also be used to infer molecular structure 4.…”
Section: A Brief Introduction To 2d‐ir Spectroscopymentioning
confidence: 99%